Gendered outgroup prejudice: An evolutionary threat management perspective on anti-immigrant bias - Ji, Tingting (Group Process Intergroup Relat, 2019)
Are male and female immigrants viewed similarly or differently? Consistent with an evolutionary threat management perspective, we suggest that the answer to this question depends upon what types of threats immigrant groups are perceived as posing. In the present study, we compared attitudes toward male and female immigrants from either a violent ecology (e.g., Syria) or a pathogen-rich ecology (e.g., Liberia). We hypothesized that people would have more negative attitudes toward male than female immigrants from a violent ecology, but that attitudes would be similar toward male and female immigrants from a pathogen-rich ecology. Internal meta-analyses of three studies (total N = 1,488) were in line with our hypothesis. They showed that attitudes toward male immigrants from a violent ecology were more negative than attitudes toward female immigrants from the same ecology. In contrast, attitudes toward male and female immigrants were similar when those immigrants came from a pathogen-rich ecology. Our findings are consistent with an evolutionary threat management perspective on outgroup prejudice and are aligned with the male warrior hypothesis: Attitudes toward male versus female outgroup members vary with the potential threats these outgroups pose.